Stable nuclear transformation of rhodophyte species Porphyridium purpureum: advanced molecular tools and an optimized method - Prasad, Binod; Lein, Wolfgang; Thiyam, General; Lindenberger, Christoph; Buchholz, Rainer; Vadakedath, Nithya (Photosynthesis Research, 2019)
A mutated phytoene desaturase (pds) gene, pds-L504R, conferring resistance to the herbicide norflurazon has been reported as a dominant selectable marker for the genetic engineering of microalgae (Steinbrenner and Sandmann in Appl Environ Microbiol 72:7477–7484, 2006; Prasad et al. in Appl Microbiol Biotechnol 98(20):8629–8639, 2014). However, this mutated genomic clone harbors several introns and the entire expression cassette including its native promoter and terminator has a length > 5.6 kb, making it unsuitable as a standard selection marker. Therefore, we designed a synthetic, short pds gene (syn-pds-int) by removing introns and unwanted internal restriction sites, adding suitable restriction sites for cloning purposes, and introduced the first intron from the Chlamydomonas reinhardtii RbcS2 gene close to the 5′end without changing the amino acid sequence. The syn-pds-int gene (1872 bp) was cloned into pCAMBIA 1380 under the control of a short sequence (615 bp) of the promoter of pds (pCAMBIA 1380-syn-pds-int). This vector and the plasmid pCAMBIA1380-pds-L504R hosting the mutated genomic pds were used for transformation studies. To broaden the existing transformation portfolio, the rhodophyte Porphyridium purpureum was targeted. Agrobacterium-mediated transformation of P. purpureum with both the forms of pds gene, pds-L504R or syn-pds-int, yielded norflurazon-resistant (NR) cells. This is the first report of a successful nuclear transformation of P. purpureum. Transformation efficiency and lethal norflurazon dosage were determined to evaluate the usefulness of syn-pds-int gene and functionality of the short promoter of pds. PCR and Southern blot analysis confirmed transgene integration into the microalga. Both forms of pds gene expressed efficiently as evidenced by the stability, tolerance and the qRT-PCR analysis. The molecular toolkits and transformation method presented here could be used to genetically engineer P. purpureum for fundamental studies as well as for the production of high-value-added compounds.
CRIS-Team Scopus Importer:2019-05-17
Keywords: Agrobacterium tumefaciens; Norflurazon-resistant; Phytoene desaturase; Porphyridium purpureum; Transformation